A boundry integral equation for the 2D external potential flow - Nasser, M.; Mohamed Murid, Ali Hassan; Saidina Amin, Norsarahaida (2006)
Based on the recently discovered second kind Fredholm integral equation for the exterior Riemann problem, a boundary integral equation is developed in this paper for the two-dimensional, irrotational, incompressible fluid flow around an airfoil without a cusped trailing edge. The solution of the integral equation contains one arbitrary real constant, which may be determined by imposing the Kutta-Joukowski condition. Comparisons between numerical and analytical values of the pressure coefficient on the surface of the NACA 0009 and NACA 0012 airfoils with zero angle of attack show a very good agreement